Membangung Customer Loyalty Melalui Service Quality, Product Quality, Islamic Business Ethic dan Customer Satisfaction - Lailia, Khusnul; Guritno, Agung (Politeknik Baubau, 2025)
Companies must provide the best service and product quality in an increasingly competitive business era to maintain and enhance customer loyalty. Business ethics based on Islamic values are also very important for building customer satisfaction, which will ultimately affect customer loyalty. This study aims to determine the influence of service quality, product quality, and Islamic business ethics on customer loyalty with customer satisfaction as an intervening variable. The observation model used is quantitative research by processing primary data obtained through the distribution of questionnaires to customers of Kaffa Konveksi X Positive Apparel. The sample in this study consisted of 100 respondents using purposive sampling technique, and the results obtained were processed using SmartPLS 4.0. The results of this study are as follows: service quality has a positive and significant effect on customer loyalty, product quality has a positive and significant effect on customer loyalty, Islamic business ethic has a positive but not significant effect on customer loyalty, customer satisfaction has a negative but not significant effect on customer loyalty, service quality has a positive and significant effect on customer satisfaction, product quality has a negative but not significant effect on customer satisfaction, islamic business ethic has a negative but not significant effect on customer satisfaction, customer satisfaction is unable to mediate the relationship between service quality, product quality, and islamic business ethic on customer loyalty. It can be concluded that service quality has a significant impact on both customer satisfaction and customer loyalty, product quality significantly affects customer loyalty, and islamic business ethics do not show a significant impact on either customer satisfaction or customer loyalty.